Echoes of the Absolute. Rainer Maria Rilke’s «Buch der Bilder» (Studia austriaca, 2016)
In this article I examine some of the key poems in Rilke’s Book of Images in an attempt to elucidate its somewhat elusive order. Moving away from the tendency to interpret this cycle of poems biographically, I use the iconography of Rilke’s prose, as well as his other poetry, to uncover a gesture that is the source of the persona’s ability to create. Following de Man, I offer that this gesture and its subsequent formulation into poetic language is akin to Hölderlin’s distinction between the ontological status of a flower and the becoming of the poetic word that sings it.